(untitled) - Worth, Richard (Indianapolis, IN., 2002)
Webster’s New World Business writing handbook provides invaluable information about key business-writing areas, including finance, scientific-technical, advertising, development, and legal and contractual; Covers not only business letters but also style and etiquette for both e-mail and memos, advertising copywriting, formats and organizational plans for proposals, resumés, and more; Explains the principles of effective procedure writing and preparing a powerful presentation; Outlines the general formats for reports; Addresses the handling of employee issues and announcements; Offers a clear, definitive glossary of the most commonly used business-writing terms.
Keywords: Commercial correspondence,Business writing; Handbooks, manuals, etc.,Handbooks, manuals, etc